Past and present anthropic environmental stress reflect high susceptibility of natural freshwater ecosystems in Romania - Iordache, Andreea Maria; Nechita, Constantin; Pluhacek, Tomas; Iordache, Mihaela; Zgavarogea, Ramona; Ionete, Roxana Elena (Environmental pollution (1987), 2020)
The concentrations of twelve heavy metals and trace elements (Cr, Mn, Co, Ni, Cu, As, Cd, Pb, Hg, Zn, Fe, and Al) in bed sediment and river freshwater that received sewage discharge, industrial wastewater inputs and mining residue were discussed. Spatial distribution, intra-annual trends and diffuse flux in 2019 in the middle and lower reaches of Olt River Basin (ORB) were investigated using inductively coupled mass spectrometry (ICP-MS) and atomic absorption spectroscopy (AAS). We applied correlation and principal component analysis (PCA) to quantify metal distribution relationship within environmental factors (pH, air temperature) and organic matter existing in the ORB. Moreover, the 87Sr/86Sr and 206Pb/207Pb isotope ratios analysis was employed to conclude the possible origin of the contamination. PCA analysis categorized metal presence in the four-component model, which explains 91% (May), 92% (July) and 93% (September) of the variance and indicates the potential origins of pollutants. The HCA and correlation analysis emphasized the relationship between trace elements, heavy metals in water and sediments and physicochemical characteristics of water. It was observed a high discrepancy in metal distribution between riverbed sediments and water body. In September, correlation indices highlighted sparse positive relationship with trace elements in water and mainly negative correlation values with trace elements from sediments. The origin of pollutants in sediments and water appear to be both natural and human-related activities. In all seasons increased the total exchangeable concentration of Ni, Cu and Zn in the sediments downstream sewage treatment plants and upstream of dams. The consideration of environmental factors and physicochemical characteristics of water is required to develop strategies for pollution management, assessment and mitigation in the actual condition of climate change. This study evaluated the heavy metals pollution in the Olt River Basin over three periods in 2019 under human-induced changes.
Keywords: ekosystém; Rumunsko; Geologic Sediments; Ecosystem; geologické sedimenty; Romania; chemické látky znečišťující vodu; těžké kovy; Metals, Heavy; Water Pollutants, Chemical; Environmental Monitoring; monitorování životního prostředí